Problems and Countermeasures of Archives Management in the New Period - Li, Kaidi (Journal of Theory and Practice of Social Science, 2023)
In recent years, with the continuous development of science and technology, archives management is becoming more and more important in the process of social development, but also brings opportunities and challenges for the development of archives management. In the new era, archives work must keep pace with The Times, to recognize the situation of social development, in order to fully reflect the value of archives management. In this paper, the current situation of archives management in the new period is analyzed, and the existing problems are identified, and the improvement measures are proposed tentatively to realize the modernization of archives management and improve the quality of archives management.